Tau acetylation at K280 is critical for propagation and an antibody targeting it prevents in vivo tau propagation: Developing topics. (7th December 2020) - Yoon, Seung‐Yong; Song, Halim; Kim, Na‐Young; Kim, Dong‐Hou
Abstract: Background: The spread of tau pathology from the transentorhinal cortex to the hippocampus and neocortex in Alzheimer's disease (AD) is explained by the prion‐like cell‐to‐cell seeding and propagation of misfolded tau aggregates. Hence, it is important to define the seeding‐ and propagation‐competent tau species and to develop targeted therapeutic antibodies. Method: Various methods like thioflavin‐T, FRET, FACS, and in vivo stereotaxic injection of AD‐derived tau aggregate fractions were used to evaluate tau aggregation, propagation, and the efficacy of an antibody to inhibit these processes. Result: Acetylation of tau at K280 is critical for the successive tau propagation processes, including secretion, aggregation, and seeding. An antibody targeting acetylated tau at K280 effectively prevented AD‐derived insoluble tau aggregates‐induced proteopathic seeding and propagation in in vitro assays and in vivo mouse brains. Conclusion: Acetylated tau at K280 is a core species of seeding and propagation, which could be a therapeutic target for AD and other tauopathies.